RETIREMENT PERCEPTION: THE IMPACT ON WORK STRESS, WORK MOTIVATION, AND EMPLOYEES’ PERFORMANCE (A STUDY IN THE SCOPE OF HASANUDDIN UNIVERSITY) - Achmad Fatri Gandrasula; Haris Maupa; Ria Mardiana Yusuf (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
The research aimed at investigating the direct or indirect effect of the retirement period perception on the work stress, work motivation, and employees’ performance approaching the retirement at Hasanuddin University. The research used the quantitative approach, in which the primary data were collected through the questionnaire from 86 respondents as the samples. The data obtained were analysed using he path analysis. The research result that the retirement period perception has the positive and significant effect on the work stress, work motivation, and employees’ performance. The work stress has the negative and significant on the employees’ performance and work motivation. Then, the work motivation has the positive and significant on the employees’ performance. The work stress in the research can mediate the negative and significant effect of the retirement period perception on the employees’ performance, whereas the work motivation can mediate the positive and significant effect of the retirement period perception. Moreover, the work motivation can also mediate the negative and significant effect of the work stress on the employees’ performance. Therefore, Hasanuddin University leadership needs to develop the employees’ positive perception on the retirement to reduce the work stress level and encourage the employees’ work motivation approaching the retirement through the training program for the retirement preparation period.